Notes on construction in mild steel arranged for the use of junior draughtsmen in the architectural and engineering professions : with illustrations from working drawings, diagrams, and tables - Fidler, Henry (Longmans' civil engineering series., 1907)
These notes offer to assist the student in the study and observation of good examples of steel construction, and in the practical application of a material which has an important position in both architectural and engineering construction.